Carbon fiber sizing agent as well as preparation method and sizing method thereof
By using components such as epoxy resin, epoxy emulsifier and modified graphene in the carbon fiber sizing agent and using the reverse emulsification method, the problem of poor stability of the emulsion type sizing agent is solved, and the mechanical properties and processing properties of the carbon fiber composite materials are improved.
Patent Information
- Application Number
- CN202411726041.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-21
AI Technical Summary
The existing emulsion type carbon fiber sizing agent has poor stability, and long-term placement will cause stratification, resulting in a degradation of performance, and the emulsifier cannot participate in the chemical reaction of the main resin, affecting the mechanical properties of carbon fiber composite materials.
The carbon fiber sizing agent is prepared by components such as epoxy resin, epoxy emulsifier and modified graphene. The emulsion type sizing agent is prepared by the reverse emulsification method to improve its stability and enable the emulsifier to participate in the curing reaction to enhance the mechanical properties of the carbon fiber composite materials.
It improves the stability of carbon fiber sizing agent, extends its service life, enhances the mechanical properties of carbon fiber composites, and improves its processing performance.
Smart Images

Figure CN119663638A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber materials, and in particular relates to a carbon fiber sizing agent and a preparation method and a sizing method thereof. Background Art
[0002] Carbon fiber is a special fiber material with a carbon mass fraction greater than 90% and stacked along the fiber axis by graphite chips. It has excellent properties such as high strength, high modulus, high temperature resistance, corrosion resistance, and fatigue resistance, and also has the softness and processability of textile fibers. Therefore, it is often used as the most important reinforcing material for advanced composite materials. For example, reinforced composite materials prepared by combining carbon fiber and epoxy resin have ultra-high specific strength and specific modulus. Its biggest advantage is that it can take into account the performance of carbon fiber and matrix material. However, due to its brittle characteristics, carbon fiber is prone to fluffing due to the cross-friction between fibers during high-speed weaving, and sometimes the carbon fiber filaments break and fall off, which significantly reduces the physical strength of the carbon fiber and even loses some of its original physical properties.
[0003] Sizing agent is an important auxiliary agent to improve the performance of carbon fiber. The sizing agent is coated on the surface of carbon fiber to form a protective film with a thickness of tens to hundreds of nanometers and a mass fraction of 0.8%-1.5%. It can greatly reduce the fiber fuzzing, fiber breakage or deformation and other undesirable phenomena produced during fiber processing, make the fiber easier to bundle, improve its reprocessing performance, and at the same time ensure that the fiber itself is not damaged.
[0004] At present, sizing agents are divided into solvent-based, water-soluble and emulsion-based types. Among them, the emulsion-based sizing agent is to continuously add water to the mixture of emulsifier and main resin or water-based main resin for stirring, and finally emulsify to obtain an emulsion with relatively high stability. In the prior art, the stability of the emulsion-based sizing agent is poor, and stratification will occur after long-term storage, which greatly reduces the performance of the sizing agent. In addition, the emulsifier used is chemically inert and cannot participate in the chemical reaction of the main resin, resulting in a decrease in the mechanical properties of the carbon fiber composite material. Therefore, it needs to be improved. Summary of the invention
[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a carbon fiber sizing agent and a preparation method and a sizing method thereof.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A carbon fiber sizing agent is prepared by comprising the following components in parts by weight: 30-50 parts of epoxy resin, 15-25 parts of epoxy emulsifier, 6-9 parts of modified graphene and 80-120 parts of distilled water; the epoxy emulsifier is epoxy resin grafted with p-aminobenzoic acid and octadecylamine; the modified graphene is graphene grafted with lysine.
[0007] In some embodiments, the epoxy emulsifier is prepared by including the following components in parts by weight: 10-15 parts of epoxy resin, 4-10 parts of p-aminobenzoic acid, and 3-8 parts of octadecylamine.
[0008] In some embodiments, the modified graphene is prepared by including the following components in parts by weight: 10-12 parts of graphene oxide and 6-8 parts of lysine.
[0009] The present invention further proposes a method for preparing a carbon fiber sizing agent, comprising the following steps: Add epoxy emulsifier and modified graphene to epoxy resin, mix evenly, place in an emulsifier, slowly and evenly add distilled water at 50-70°C while emulsifying at high speed, the speed of the emulsifier is 10000-14000r / min, and after phase inversion, quickly add the remaining distilled water to obtain a carbon fiber sizing agent.
[0010] In some embodiments, the method for preparing the epoxy emulsifier comprises the following steps: Add p-aminobenzoic acid and octadecylamine to ethylene glycol monobutyl ether and ethanol, add epoxy resin, continue stirring and heat to 40°C under nitrogen atmosphere for 20-40 minutes, then heat to 110-120°C and react for 10-15 hours. After the reaction is completed, cool and wash to obtain epoxy emulsifier.
[0011] Furthermore, the volume ratio of ethylene glycol monobutyl ether to ethanol is 2:1.
[0012] In some embodiments, the method for preparing the modified graphene comprises the following steps: Graphene oxide was added to deionized water, ultrasonically treated, lysine was added, the pH value was adjusted to 7 using 15wt% sodium hydroxide solution, heated to 50°C, stirred and reacted for 20-25h, cooled after completion, centrifuged and washed to obtain modified graphene oxide.
[0013] Furthermore, the amount of graphene oxide added to deionized water is 2-4 mg / mL.
[0014] Furthermore, the power of the ultrasonic treatment is 200W and the time is 20-40min.
[0015] The present invention also provides a sizing method, comprising the following steps: Cleaning and surface treating the carbon fiber; Take the carbon fiber sizing agent and add it into the impregnation tank, and immerse the carbon fiber into the impregnation tank for 60-90 seconds; After the impregnation is completed, the carbon fiber is taken out and hot air drying is performed. The hot air drying temperature is 120° C. and the time is 5-15 minutes to obtain the sizing carbon fiber.
[0016] The beneficial effects achieved by the present invention are as follows: The epoxy resin is modified by introducing the hydrophilic segment p-aminobenzoic acid and the lipophilic segment octadecylamine to prepare the epoxy emulsifier, and the emulsion type carbon fiber sizing agent is prepared by the phase inversion emulsification method to improve the stability of the sizing agent; and the epoxy emulsifier can also participate in the curing reaction to improve the mechanical properties of the carbon fiber after sizing; in addition, the modified graphene is grafted with hydrophilic lysine, making the originally hydrophobic graphene amphiphilic, which not only stabilizes the emulsion, but also can spread on the carbon fiber surface to improve the interfacial strength of the carbon fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a graph showing the interlaminar shear performance test results of Examples 1-3 of the present invention and Comparative Examples 1 and 2.
[0018] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0020] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0021] In view of the deficiencies in the prior art mentioned in the background technology, the present invention comprises the following components in parts by weight: 30-50 parts of epoxy resin, 15-25 parts of epoxy emulsifier, 6-9 parts of modified graphene and 80-120 parts of distilled water; the epoxy emulsifier is epoxy resin grafted with p-aminobenzoic acid and octadecylamine; the modified graphene is graphene grafted with lysine.
[0022] Among them, a non-ionic epoxy emulsifier is prepared by grafting a hydrophilic segment of p-aminobenzoic acid and a lipophilic segment of octadecylamine on an epoxy resin, and by controlling the lengths of the hydrophilic segment and the lipophilic segment, the epoxy emulsifier has a good emulsification effect and can also participate in the curing reaction, thereby improving the mechanical properties of the carbon fiber after sizing. In addition, graphene oxide has amphiphilicity after being grafted with lysine, which can stabilize the emulsion and improve the stability of the sizing agent. At the same time, the modified graphene can also spread on the surface of the carbon fiber to improve the interface strength of the carbon fiber.
[0023] In some embodiments, the epoxy emulsifier is prepared by including the following components in parts by weight: 10-15 parts of epoxy resin, 4-10 parts of p-aminobenzoic acid, and 3-8 parts of octadecylamine.
[0024] In some embodiments, the modified graphene is prepared by including the following components in parts by weight: 10-12 parts of graphene oxide and 6-8 parts of lysine.
[0025] In some embodiments, a method for preparing a carbon fiber sizing agent comprises the following steps: Add epoxy emulsifier and modified graphene to epoxy resin, mix evenly, place in an emulsifier, slowly and evenly add distilled water at 50-70°C while emulsifying at high speed, the speed of the emulsifier is 10000-14000r / min, and after phase inversion, quickly add the remaining distilled water to obtain a carbon fiber sizing agent.
[0026] In some embodiments, the preparation method of the epoxy emulsifier comprises the following steps: Add p-aminobenzoic acid and octadecylamine to ethylene glycol monobutyl ether and ethanol, add epoxy resin, continue stirring and heat to 40°C under nitrogen atmosphere for 20-40 minutes, then heat to 110-120°C and react for 10-15 hours. After the reaction is completed, cool and wash to obtain epoxy emulsifier.
[0027] In some embodiments, the volume ratio of ethylene glycol monobutyl ether to ethanol is 2:1.
[0028] In some embodiments, the method for preparing modified graphene comprises the following steps: Graphene oxide was added to deionized water, ultrasonically treated, lysine was added, the pH value was adjusted to 7 using 15wt% sodium hydroxide solution, heated to 50°C, stirred and reacted for 20-25h, cooled after completion, centrifuged and washed to obtain modified graphene oxide.
[0029] In some embodiments, graphene oxide is added to deionized water in an amount of 2-4 mg / mL.
[0030] In some embodiments, the ultrasonic treatment is performed at a power of 200 W and for a time of 20-40 min.
[0031] A sizing method comprises the following steps: Cleaning and surface treating the carbon fiber; Take the carbon fiber sizing agent and add it into the impregnation tank, and immerse the carbon fiber into the impregnation tank for 60-90 seconds; After the impregnation is completed, the carbon fiber is taken out and hot air drying is performed. The hot air drying temperature is 120° C. and the time is 5-15 minutes to obtain the sizing carbon fiber.
[0032] The present invention will be further described below by way of specific embodiments.
[0033] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0034] The sources of some materials in the examples are as follows: Epoxy resin, model: E51, was purchased from Jiangsu Sanmu Chemical Co., Ltd.
[0035] p-Aminobenzoic acid, CAS number: 205-753-0, was purchased from Jiangsu Pules Biotechnology Co., Ltd.
[0036] Octadecylamine, CAS No.: 124-30-1, was purchased from Hubei Longxin Chemical Industry Co., Ltd.
[0037] Lysine, CAS number: 56-87-1, was purchased from Jiangsu Bosite Chemical Technology Co., Ltd.
[0038] Graphene oxide was prepared by Hummers method.
[0039] Example 1 A carbon fiber sizing agent is prepared by including the following components in parts by weight: 30 parts of epoxy resin, 15 parts of epoxy emulsifier, 6 parts of modified graphene, and 80 parts of distilled water. The epoxy emulsifier is prepared by including the following components in parts by weight: 10 parts of epoxy resin, 4 parts of p-aminobenzoic acid, and 3 parts of octadecylamine. The modified graphene is prepared by including the following components in parts by weight: 10 parts of graphene oxide and 6 parts of lysine.
[0040] A method for preparing a carbon fiber sizing agent comprises the following steps: S1. Add p-aminobenzoic acid and octadecylamine to ethylene glycol monobutyl ether and ethanol in a volume ratio of ethylene glycol monobutyl ether to ethanol of 2:1, add epoxy resin, and heat to 40°C for 20 min under a nitrogen atmosphere with continuous stirring, then heat to 110°C for reaction for 10 h. After the reaction is completed, cool and wash to obtain an epoxy emulsifier; S2, adding graphene oxide in an amount of 2 mg / mL to deionized water, ultrasonically treating at a power of 200 W for 20 min, adding lysine, adjusting the pH value to 7 with a 15 wt % sodium hydroxide solution, heating to 50° C., stirring and reacting for 20 h, cooling after completion, centrifuging and washing to obtain modified graphene oxide; S3. Add epoxy emulsifier and modified graphene to epoxy resin, mix evenly, place in an emulsifier, slowly and evenly add distilled water at 50°C while emulsifying at high speed. The speed of the emulsifier is 10000r / min. After phase inversion, quickly add the remaining distilled water to obtain a carbon fiber sizing agent.
[0041] A sizing method comprises the following steps: The carbon fiber is cleaned and surface treated, and the carbon fiber sizing agent is added to the impregnation tank. The carbon fiber is immersed in the impregnation tank for 60 seconds. After the impregnation is completed, the carbon fiber is taken out and hot air dried at a temperature of 120°C for 5 minutes to obtain the sized carbon fiber.
[0042] Example 2 A carbon fiber sizing agent is prepared by including the following components in parts by weight: 50 parts of epoxy resin, 25 parts of epoxy emulsifier, 9 parts of modified graphene, and 120 parts of distilled water. The epoxy emulsifier is prepared by including the following components in parts by weight: 15 parts of epoxy resin, 10 parts of p-aminobenzoic acid, and 8 parts of octadecylamine. The modified graphene is prepared by including the following components in parts by weight: 12 parts of graphene oxide and 8 parts of lysine.
[0043] A method for preparing a carbon fiber sizing agent comprises the following steps: S1. Add p-aminobenzoic acid and octadecylamine to ethylene glycol monobutyl ether and ethanol in a volume ratio of 2:1, add epoxy resin, and heat to 40° C. for 40 min under a nitrogen atmosphere with continuous stirring, then heat to 120° C. for 15 h. After the reaction is completed, cool and wash to obtain an epoxy emulsifier. S2, adding graphene oxide in an amount of 4 mg / mL to deionized water, ultrasonically treating at a power of 200 W for 40 min, adding lysine, adjusting the pH value to 7 with a 15 wt % sodium hydroxide solution, heating to 50° C., stirring and reacting for 25 h, cooling after completion, centrifuging and washing to obtain modified graphene oxide; S3. Add epoxy emulsifier and modified graphene to epoxy resin, mix evenly, place in an emulsifier, slowly and evenly add distilled water at 70°C while emulsifying at high speed. The speed of the emulsifier is 14000r / min. After phase inversion, quickly add the remaining distilled water to obtain a carbon fiber sizing agent.
[0044] A sizing method comprises the following steps: The carbon fiber is cleaned and surface treated, and the carbon fiber sizing agent is added to the impregnation tank. The carbon fiber is immersed in the impregnation tank for 90 seconds. After the impregnation is completed, the carbon fiber is taken out and hot air dried at a temperature of 120°C for 15 minutes to obtain the sized carbon fiber.
[0045] Example 3 A carbon fiber sizing agent is prepared by including the following components in parts by weight: 40 parts of epoxy resin, 20 parts of epoxy emulsifier, 7 parts of modified graphene, and 100 parts of distilled water. The epoxy emulsifier is prepared by including the following components in parts by weight: 13 parts of epoxy resin, 7 parts of p-aminobenzoic acid, and 6 parts of octadecylamine. The modified graphene is prepared by including the following components in parts by weight: 11 parts of graphene oxide and 7 parts of lysine.
[0046] A method for preparing a carbon fiber sizing agent comprises the following steps: S1. Add p-aminobenzoic acid and octadecylamine to ethylene glycol monobutyl ether and ethanol in a volume ratio of 2:1, add epoxy resin, and heat to 40° C. for 30 min under a nitrogen atmosphere with continuous stirring, then heat to 115° C. for reaction for 13 h. After the reaction is completed, cool and wash to obtain an epoxy emulsifier; S2, adding graphene oxide in an amount of 3 mg / mL to deionized water, ultrasonically treating at a power of 200 W for 30 min, adding lysine, adjusting the pH value to 7 with a 15 wt % sodium hydroxide solution, heating to 50° C., stirring and reacting for 23 h, cooling after completion, centrifuging and washing to obtain modified graphene oxide; S3. Add epoxy emulsifier and modified graphene to epoxy resin, mix evenly, place in an emulsifier, slowly and evenly add distilled water at 60°C while emulsifying at high speed. The speed of the emulsifier is 12000r / min. After phase inversion, quickly add the remaining distilled water to obtain a carbon fiber sizing agent.
[0047] A sizing method comprises the following steps: The carbon fiber is cleaned and surface treated, and the carbon fiber sizing agent is added to the impregnation tank. The carbon fiber is immersed in the impregnation tank for 80 seconds. After the impregnation is completed, the carbon fiber is taken out and hot air dried at a temperature of 120°C for 10 minutes to obtain the sized carbon fiber.
[0048] Comparative Example 1 This comparative example provides a carbon fiber sizing agent, which differs from Example 1 only in that the preparation components of the sizing agent do not include modified graphene oxide, and the remaining components and component contents are the same as those in Example 1.
[0049] Comparative Example 2 This comparative example provides a carbon fiber sizing agent, which differs from Example 1 only in that the commercial emulsifier polyoxyethylene octylphenol ether OP-10 is used in the preparation components of the sizing agent instead of the epoxy emulsifier, and the remaining components and component contents are the same as those in Example 1.
[0050] Experimental Example 1 The sizing agents of Examples 1-3 of the present invention and Comparative Examples 1 and 2 were tested for stability, and the specific method was as follows: (1) Storage stability: Take 300 mL of sizing agent in a beaker and store it at room temperature for 6 months to observe whether the sizing agent will demulsify and stratify; (2) High temperature stability: Take 300 mL of sizing agent in a beaker and place it in a constant temperature drying oven at 60°C. Observe whether the sizing agent emulsion will demulsify and stratify over 7 days.
[0051] (3) Mechanical stability: Take 300 mL of sizing agent and place it in a centrifuge. Centrifuge it at 3000 r / min for 30 min and observe whether there is precipitation.
[0052] The results are shown in Table 1: Table 1
[0053] Experimental Example 2 The interlaminar shear performance (ILSS) of the carbon fiber composite material was tested on the sizing carbon fibers prepared in Examples 1-3 of the present invention and Comparative Examples 1 and 2. A carbon fiber composite material plate with a carbon fiber content of 60% was prepared using TDE-85 epoxy resin as a matrix resin. The plate was cut into specified sizes according to the standard and then tested on a universal mechanical testing machine.
[0054] Figure 1 The interlaminar shear performance test results are shown in the figure. The interlaminar shear strengths of Examples 1-3 are 84.7 MPa, 86.2 MPa, and 87.8 MPa, respectively, those of Comparative Example 1 are 71.5 MPa, and those of Comparative Example 2 are 79.3 MPa. The interlaminar shear strength of Comparative Example 1 is the smallest, which shows that the addition of modified graphene oxide can improve the interface strength of carbon fiber, thereby improving the interlaminar shear performance of carbon fiber composite materials. The interlaminar shear strength of Comparative Example 2 is reduced by 6.4% compared with that of Comparative Example 1, which shows that the epoxy emulsifier can improve the mechanical properties of carbon fiber after sizing.
[0055] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A carbon fiber sizing agent, characterized in that: The invention comprises the following components in parts by weight: 30-50 parts of epoxy resin, 15-25 parts of epoxy emulsifier, 6-9 parts of modified graphene and 80-120 parts of distilled water; the epoxy emulsifier is epoxy resin grafted with p-aminobenzoic acid and octadecylamine; and the modified graphene is graphene grafted with lysine.
2. The carbon fiber sizing agent according to claim 1, characterized in that The epoxy emulsifier is prepared by including the following components in parts by weight: 10-15 parts of epoxy resin, 4-10 parts of p-aminobenzoic acid, and 3-8 parts of octadecylamine.
3. The carbon fiber sizing agent according to claim 1, characterized in that: The modified graphene is prepared by comprising the following components in parts by weight: 10-12 parts of graphene oxide and 6-8 parts of lysine.
4. A method for preparing a carbon fiber sizing agent according to claim 1, characterized in that: The steps include: Add epoxy emulsifier and modified graphene to epoxy resin, mix evenly, place in an emulsifier, slowly and evenly add distilled water at 50-70°C while emulsifying at high speed, the speed of the emulsifier is 10000-14000r / min, and after phase inversion, quickly add the remaining distilled water to obtain a carbon fiber sizing agent.
5. The preparation method according to claim 4, characterized in that: The preparation method of the epoxy emulsifier comprises the following steps: Add p-aminobenzoic acid and octadecylamine to ethylene glycol monobutyl ether and ethanol, add epoxy resin, continue stirring and heat to 40°C under nitrogen atmosphere for 20-40 minutes, then heat to 110-120°C and react for 10-15 hours. After the reaction is completed, cool and wash to obtain epoxy emulsifier.
6. The preparation method according to claim 5, characterized in that: The volume ratio of the ethylene glycol monobutyl ether to ethanol is 2:
1.
7. The preparation method according to claim 4, characterized in that: The preparation method of the modified graphene comprises the following steps: Graphene oxide was added to deionized water, ultrasonically treated, lysine was added, the pH value was adjusted to 7 using 15wt% sodium hydroxide solution, heated to 50°C, stirred and reacted for 20-25h, cooled after completion, centrifuged and washed to obtain modified graphene oxide.
8. The preparation method according to claim 7, characterized in that: The amount of graphene oxide added to deionized water is 2-4 mg / mL.
9. The preparation method according to claim 7, characterized in that: The power of the ultrasonic treatment is 200W, and the time is 20-40min.
10. A sizing method for a carbon fiber sizing agent according to claim 1, characterized in that: The steps include: Cleaning and surface treating the carbon fiber; Take the carbon fiber sizing agent and add it into the impregnation tank, and immerse the carbon fiber into the impregnation tank for 60-90 seconds; After the impregnation is completed, the carbon fiber is taken out and hot air drying is performed. The hot air drying temperature is 120° C. and the time is 5-15 minutes to obtain the sizing carbon fiber.
Citation Information
Cited By
Preparation method of flame-retardant and fire-resistant epoxy resin carbon fiber prepreg
CN121343223A